Determinants of bank profitability in Pakistan: a case study of Pakistani banking sector - Khan, Faisal (International Digital Organization for Scientific Information (I D O S I), 2011)
In Pakistan, the banking performance is influenced by deregulation, financial modernization and technological improvement. Financial sector is the back bone of the sustainable economic growth. So it is very important to assess the negative shocks in order to maintain the financial stability in Pakistan. This study is conducted to find out the main determinants of banks profitability considering the bank specific variables. The analysis has been conducted on 16 banks on the basis of availability of data over the period 2000 to 2010. This paper uses fixed effect model and random effect model to examine the impacts of net interest margin, profit to asset ratio, bank size, loan growth, non-interest earning, overhead expenses, taxation, insider lending, operating expenses, non-performing loans, return on asset ratio and deposit to asset ratio. The empirical results show a strong association between some banks specific variables and their profitability. The variables of deposit to asset ratio, deposit to loans ratio, loans to asset ratio, loan growth, non-performing loans, net interest margin, tax, non-interest income and return on asset are the main determinates of banks profitability in our analysis. Furthermore, the banks are divided into two groups according to their market capitalization i.e. large and small banks.. LNG is significant at 1% with positive value (3.56734) indicating that with loan growth, the bank’s capacity to earn more in the market enhances. In case of small banks, the variable of loan growth is insignificant. Hence, the non-performing loans are seriously reducing the profitability of banks in small banks.